Sistema de cubiertas verdes para el bioclimatísmo en la carrera de Ingeniería Ambiental - Bravo Morán, Angélica Lucrecia (2019)
The research focused temperature and relative humidity on two of houses; one was a traditional house and the other house with the implementation of a system of green roofs with hydroponic crops the second one was carried out in the Polytechnic Forest of the MFL ESPAM. It was carried out as comparative investigation to both house for the evaluation of the efficiency of the system of green roof in which statiscal data were obtained from each temperature capture were obtained and the relative humidity. Ornamental plants and vegetables were used for the cultivation, these plants were moving in the tubes PVC (nutrients were applied P-K-Ca) and used in the NFT system (nutrient film technique). This technique consisted of the re-circulation of the nutrient solution through several PVC channels, which with the help of a pump the nutrient solution returned throughout the circuit. The recirculation supplies the necessary nutrients to the plants through the roost that hang from the baskets of the container so that the plant develops and grows appropriately. The results of the obtained objectives showed that by installing these systems if it was possible to maintain a temperature reduction, thus giving a significant difference of 1 between both houses in which was determined the temperature degree and the relative humidity percentages.